The Vision of the Prophet Muhammad (PBUH) in Wakefulness and Dreams and the Associated Legal Rulings - Othman Abbas Khalaf Hussein (Islamic Sciences Journal, 2025)
Scholars have traditionally built upon the work of their predecessors in exploring certain theological issues, substantiating them with both textual and rational evidence. Among these issues is the matter of seeing the Prophet Muhammad (PBUH) in wakefulness and dreams. This research focuses on the vision of the Prophet in dreams, and on whether such visions can also occur in wakefulness, as discussed by Imam al-Bukhari, whose views are examined in this study. Additionally, the research addresses whether one who sees the Prophet (PBUH) can be considered a Companion (Sahabi), a topic debated among scholars.